2007
DOI: 10.1021/nl063006g
|View full text |Cite
|
Sign up to set email alerts
|

Raman Spectral Probing of Electronic Transition Energy Eii Variation of Individual SWNTs under Torsional Strain

Abstract: We present herein a rational approach to probe the torsional strain-induced electronic transition energy Eii variation of individual SWNTs by resonant Raman spectroscopy (RRS). When a SWNT was manipulated by AFM tip through a path perpendicular to SWNT axis, both torsional and uniaxial strain would be introduced in SWNTs. Under the torsional strain, resonant Raman spectral mapping along a SWNT detected an M-shaped frequency (omegaRBM) and W-shaped intensity (IS) variation of radial breathing mode (RBM) spectra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 17 publications
(28 reference statements)
3
24
0
2
Order By: Relevance
“…Actually, it has been shown that RBM is strongly dependent on the kind of deformation imposed on the tubes. 15 Figure 3 shows the Raman spectra of pristine and Siimplanted DWNTs, in the region of the disorder-induced D band, and the G band. Regardless of the laser energy used for excitation, the D band is very weak in the Raman spectra of the pristine samples, indicating that the samples are of high crystalline quality.…”
Section: Rbm Of Inner Vs Outer Tubesmentioning
confidence: 99%
“…Actually, it has been shown that RBM is strongly dependent on the kind of deformation imposed on the tubes. 15 Figure 3 shows the Raman spectra of pristine and Siimplanted DWNTs, in the region of the disorder-induced D band, and the G band. Regardless of the laser energy used for excitation, the D band is very weak in the Raman spectra of the pristine samples, indicating that the samples are of high crystalline quality.…”
Section: Rbm Of Inner Vs Outer Tubesmentioning
confidence: 99%
“…Its diameter of 1.12 nm agrees well with that determined by the AFM. The map B demonstrates unusually broad PL in the region of (11,7), (12,5) and (10,9)-tubes [11]. Note that the diameters of these tubes (∼1.2 nm) are definitely smaller than the AFM value (∼1.6 nm).…”
Section: Combination Of Afm and Pl Imagesmentioning
confidence: 93%
“…Local perturbations such as sharp bends or break sites are also expected to strongly affect the electronic properties of SWNTs. For instance, Gao et al have shown the influence of torsional strain on the electronic transition energies after AFM manipulation [5]. Here, we describe in detail an approach which combines AFM and PL microscopy to investigate individual and aggregated SWNTs on surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the local DOS at the Fermi level decreased and a bandgap formed, which caused the drastic decrease of the conductivity. [101,102] The change of local DOS can be detected from the tunneling spectroscopy by STM measurement of a mechanically distorted SWNT. [103] Moreover, torsional deformation can also alter the electronic properties of CNTs.…”
Section: Mechanical Deformation Junctionsmentioning
confidence: 99%